2004
DOI: 10.2172/910954
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review of the Effects of Radiation and Temperature on the Aging of Concrete

Abstract: The open literature and accessible United States Department of Energy-sponsored reports were reviewed for the effects of radiation and temperature on concrete. No effects of radiation were found for exposures less than 10 10 neutron/cm 2 or 10 10 Gy gamma for periods less than 50 years. Reductions in compressive and tensile strength and a marked increase in volume are reported for exposures greater than 10 20 neutron/cm 2 or 10 10 rads of gamma. There are conflicting reports of damage for doses in the middle r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 36 publications
0
30
0
2
Order By: Relevance
“…The concrete is constantly subjected to aging and deterioration under combined thermochemo-hygro-mechanical effects, which often cause chemical and physical alteration of the concrete and result in excessive cracking, spalling and loss of strength [1,2]. SNF storage concrete is also susceptible to severely elevated temperatures during accident conditions and extreme events, which can lead to catastrophic fracture failure [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The concrete is constantly subjected to aging and deterioration under combined thermochemo-hygro-mechanical effects, which often cause chemical and physical alteration of the concrete and result in excessive cracking, spalling and loss of strength [1,2]. SNF storage concrete is also susceptible to severely elevated temperatures during accident conditions and extreme events, which can lead to catastrophic fracture failure [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The following description of the TN dry storage casks is based on the USNRC Safety Evaluation Report for TN-32 (USNRC 1996) and the TN Safety Analysis Reports for TN-32 (Transnuclear Inc. 2002, 2004 and TN-68 (Transnuclear Inc. 2005). …”
Section: System Descriptionmentioning
confidence: 99%
“…For normal operation or any other long-term period, Subsection CC-3400 of ASME Section III, Division 2, specifies that the concrete temperature limits shall not exceed 66°C (150°F) except for local areas, such as around penetrations, which are not allowed to exceed 93°C (200°F). Also, a gamma radiation dose of 10 10 rads may cause significant reduction of strength (Fillmore 2004). If significant equipment loads are supported by concrete exposed to temperatures exceeding 66°C (150°F) and/or gamma dose above 10 10 rads, an evaluation is to be made of the ability to withstand the postulated design loads.…”
Section: Lead Cask Inspectionmentioning
confidence: 99%
“…The effects of radiation on concrete have been addressed in numerous reports, including Clark (1958) [1], Hilsdorf et al (1978) [2], and Fillmore (2004) [3]. The most often cited is the work by Hilsdorf et al, which concluded that, for some concretes, neutron fluence of 1.0 × 10 19 n/cm 2 may cause a reduction in compressive and tensile strength and a marked increase in volume.…”
Section: Introductionmentioning
confidence: 99%